Implikasi Penundaan Kontrak Akibat Kondisi Force Majuere dalam Pandemi Covid 19 (International Forum of Researchers and Lecturers, 2025)
The research aims to analyze the form of contract delay in the Civil Code and outline the implications of contract delay due to force conditions in the Covid-19 pandemic. To answer this problem, normative legal research methods or library research are used. This normative type of research uses qualitative analysis, namely by explaining existing data with words or statements sourced from prime legal materials, secondary legal materials and tertiary legal materials. Data obtained from the literature will be analyzed deductively. Analysis is a method of analyzing general legal knowledge data obtained from laws and literature and then implemented on the problems raised, so that answers to specific problems are obtained. The results of the research show that the form of contract delay is regulated in articles 1244-1245 of the Civil Code which determines that force majeure can eliminate the element of default in the agreement, as long as the force force actually occurs and prevents one of the parties from carrying out its obligations, the type of contract delay is a contract in banking institution agreements, contracts in certain collateral imposition agreements, and contracts in business agreements. The implications of contract delays due to force majeure conditions in the Covid-19 pandemic where actions occur by not carrying out or delaying carrying out the achievements stated in the contract resulting in default and ultimately civil legal disputes between the parties involved in the contract. Dispute resolution through court or litigation refers to procedural law regarding the requirements under which a dispute or legal action can be submitted and the efforts that can be taken by the parties. as for preferences for conflict resolution (ADR) or non-litigation or preferences for conflict resolution using mediation, arbitration and negotiation methods